Corporate Social Responsibility in Improving the Quality of Public Education - Masitah Pohan (RIRAI Publisher, 2022)
Social responsibility (CSR) is generally defined as how companies meet the expectations of shareholders and stakeholders while balancing social, environmental and economic objectives. The interest of several companies to develop the educational community through CSR activities is very important for the education community. Especially since the Law on PT. 40 of 2007, CSR is getting stronger. PTs that do business or manage natural resources in this area must be responsible for their social and environmental behavior (Article 74:1). Therefore, as part of efforts to achieve transparency and accountability of the government, it is necessary to find an appropriate mechanism to oblige the government to maintain fiscal balance. Data collection in a prescribed legal manner. The results of the study indicate that efforts to create synergies between CSR and the education community are a strategic step for companies, whose benefits are directly felt by the communities in which they are founded. The company's sensitivity to education continues to pay off. The company also has a social responsibility to help solve social, economic and environmental problems facing society.